Eating, Drinking: Surviving The International Year of Global Understanding - IYGU - Jackson, Peter; Spiess, Walter E.L; Sultana, Farhana (SpringerBriefs in Global Understanding,, 2016)
This publication addresses the global challenges of food and water security in a rapidly changing and complex world. The essays highlight the links between bio-physical and socio-cultural processes, making connections between local and global scales, and focusing on the everyday practices of eating and drinking, essential for human survival. Written by international experts, each contribution is research-based but accessible to the general public.